2021
DOI: 10.1155/2021/7962630
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lianhuaqingwen Capsules for the Prevention of Coronavirus Disease 2019: A Prospective Open-Label Controlled Trial

Abstract: Coronavirus disease 2019 (COVID-19) has become a global pandemic. Community and close contact exposures continue to drive the COVID-19 pandemic. There is no confirmed effective treatment for suspected cases and close contacts. Lianhuaqingwen (LH) capsules, a repurposed Chinese herbal product that is currently on the market, have proven effective for influenza and COVID-19. To determine the safety and efficacy of LH capsules for the prevention of COVID-19, we conducted a prospective open-label controlled trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…A previous prospective trial found that the positive rate of SARS-CoV-2 in the LHQW treatment group was significantly lower than that in a non-LHQW group. However, limitations such as small research dimensions and low incidence of positivity (13 in a total of 1,976 subjects) suggested that further studies on a larger scale are necessary to validate LHQW as an effective and safe option for COVID-19 close contacts ( Gong et al, 2021 ). Therefore, we performed this large-scale study to further validate the effect of LHQW.…”
Section: Discussionmentioning
confidence: 99%
“…A previous prospective trial found that the positive rate of SARS-CoV-2 in the LHQW treatment group was significantly lower than that in a non-LHQW group. However, limitations such as small research dimensions and low incidence of positivity (13 in a total of 1,976 subjects) suggested that further studies on a larger scale are necessary to validate LHQW as an effective and safe option for COVID-19 close contacts ( Gong et al, 2021 ). Therefore, we performed this large-scale study to further validate the effect of LHQW.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed that in addition to the standard of care (SOC), LHQW improved the clinical symptoms of COVID-19 (including fever, cough, expectoration, and shortness of breath) and significantly shorted the duration of fever ( 8 - 10 ). A real-world study on the administration of LHQW to prevent COVID-19 in quarantined people confirmed that the positivity rate of SARS-CoV-2 nucleic acid in nasal and throat swabs of participants was significantly lower in the LHQW group than that in the control group ( 11 ). In summary, LHQW played an active role in the prevention and control of COVID-19 during the outbreak of the epidemic in China.…”
Section: Introductionmentioning
confidence: 98%
“…[8] For thousands of years, traditional Chinese medicine has been widely used for the prevention and treatment of diseases. [9,10] In 2003, Lianhua Qingwen (LHQW) was commonly used to treat severe acute respiratory syndrome. [11] In recent decades, it has been widely used for the treatment of viral influenza, pneumonia caused by coronavirus, the common cold, and other diseases.…”
Section: Introductionmentioning
confidence: 99%